Oleandrin: A cardiac glycosides with potent cytotoxicity - Kumar, Arvind; De, Tanmoy; Mishra, Amrita; Mishra, Arun K. (Pharmacognosy Reviews)
Cardiac glycosides are used in the treatment of congestive heart failure and arrhythmia. Current trend shows use of some cardiac glycosides in the treatment of proliferative diseases, which includes cancer. Nerium oleander L. is an important Chinese folk medicine having well proven cardio protective and cytotoxic effect. Oleandrin (a toxic cardiac glycoside of N. oleander L.) inhibits the activity of nuclear factor kappa‑light‑chain‑enhancer of activated B chain (NF‑κB) in various cultured cell lines (U937, CaOV3, human epithelial cells and T cells) as well as it induces programmed cell death in PC3 cell line culture. The mechanism of action includes improved cellular export of fibroblast growth factor‑2, induction of apoptosis through Fas gene expression in tumor cells, formation of superoxide radicals that cause tumor cell injury through mitochondrial disruption, inhibition of interleukin‑8 that mediates tumorigenesis and induction of tumor cell autophagy. The present review focuses the applicability of oleandrin in cancer treatment and concerned future perspective in the area.
Keywords: Cardiac glycosides; cytotoxicity; oleandrin